Sense of coherence and childbearing choices: A cross sectional survey. Issue 11 (November 2015) - Ferguson, Sally; Davis, Deborah; Browne, Jenny; Taylor, Jan
Abstract: Background: as concern for increasing rates of caesarean section and interventions in childbirth in Western countries mounts, the utility of the risk approach (inherent in the biomedical model of maternity care) is called into question. The theory of salutogenesis offers an alternative as it focuses on the causes of health rather than the causes of illness. Sense of coherence (SOC), the cornerstone of salutogenic theory, is a predictive indicator of health. We hypothesised that there is a relationship between a woman׳s SOC and the childbirth choices she makes in pregnancy. Methods: the study aims to investigate the relationship between SOC and women׳s pregnancy and anticipated labour choices. A cross sectional survey was conducted where eligible women completed a questionnaire that provided information on SOC scores, Edinburgh Postnatal Depression (EPDS) scores, Support Behaviour Inventory (SBI) scores, pregnancy choices and demographics. Findings: 1074 pregnant women completed the study. Compared to women with low SOC, women with high SOC were older, were less likely to identify pregnancy conditions, had lower EPDS scores and higher SBI scores. SOC was not associated with women׳s pregnancy choices. Conclusion: this study relates SOC to physical and emotional health in pregnancy as women with high SOC were less likely to identify pregnancy conditions, had less depressive symptoms and perceived higher levels of support compared to women with low SOC. Interestingly, SOC was not associated with pregnancy choices known to increase normal birth rates. More research is required to explore the relationship between SOC and women׳s birthing outcomes. Highlights: Normal birth rates are falling. Sense of coherence (SOC) is a predictive indicator of health. SOC is related to physical and emotional health in pregnancy. SOC was not found to be associated with pregnancy choices known to increase normal birth rates. More research is required to explore the relationship between SOC and women׳s birthing outcomes.